2013
DOI: 10.1002/ange.201308455
|View full text |Cite
|
Sign up to set email alerts
|

Selective Palladium‐Catalyzed Aminocarbonylation of Olefins with Aromatic Amines and Nitroarenes

Abstract: Eine Vielzahl an Olefinen kann in Gegenwart eines Pd‐basierten Katalysatorsystems und von (hetero)aromatischen Aminen oder Nitroarenen glatt, in guten Ausbeuten und oft mit hoher Regioselektivität in synthetisch nützliche Amide überführt werden (siehe Schema). Kombiniert man dieses atomeffiziente Verfahren mit gängigen Funktionalisierungen der Produkte, hat man einen effizienten Zugang zu Chinolinen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…For example, as mentioned in chapter 8.1.3, the groups of Baran 432 and Thomas 430,431 already reported on the selective homogeneous Fecatalyzed hydroamination of olefins with nitroarenes. In addition, the groups of Hu, 444,445 Wu, 446 Driver 447 and Beller 448 contributed to the field. However, the reduction of the nitro moiety is either stoichiometric or catalyzed by Pd-based systems.…”
mentioning
confidence: 99%
“…For example, as mentioned in chapter 8.1.3, the groups of Baran 432 and Thomas 430,431 already reported on the selective homogeneous Fecatalyzed hydroamination of olefins with nitroarenes. In addition, the groups of Hu, 444,445 Wu, 446 Driver 447 and Beller 448 contributed to the field. However, the reduction of the nitro moiety is either stoichiometric or catalyzed by Pd-based systems.…”
mentioning
confidence: 99%
“…To overcome these problems, recent research on the amide synthesis has paid more attention to the transition-metal-promoted direct chemical transformation of readily available nitroarenes. 9−14 For instance, the groups of Beller, 9 Driver, 10 and Wu 11 described the Pdcatalyzed aminocarbonylation of olefins or arenes with nitroarenes for the synthesis various amides, whereas Hu et al 12 and Zeng et al 13 reported the Ni-catalyzed, Cr-catalyzed, or Mn-mediated reductive amidation of nitroarenes with carboxylic acid esters, Boc-protected secondary amides, or tertiary amides (Scheme 1b). In the latter protocols, Zn, Mn, and Mg metals were used as reductants to reduce nitroarenes to more reactive nitrogen-containing intermediates (e.g., nitrosoarenes, N-aryl hydroxylamines, azoarenes, and azoxyarenes) for subsequent amidation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8 The only example of alkylamide synthesis by reductive aminocarbonylation was reported by Beller, who disclosed a Pd-catalyzed coupling of terminal alkenes with nitroarenes under syngas pressure to provide N-aryl alkylamides (Scheme 1c). 9 Here, the range of accessible products was limited by the fact that only monosubstituted alkenes were amenable to coupling. Recently, Hu also furnished alkylamides through reductive transamidation between nitroarenes and amides.…”
mentioning
confidence: 99%